Hubungan Patronase Petani dengan Pengepul Komoditas Pertanian di Desa Datar Ajab Kabupaten Hulu Sungai Tengah - Amalia, Nur; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2026)
The diversity of agricultural commodities in Datar Ajab Village, Hulu Sungai Tengah (HST) Regency presents economic potential. The cultivation of these agricultural commodities is an effort to meet daily needs, but the sale of agricultural commodities by farmers is still dominated by local collectors in the village as an extension before reaching consumers in the market. This study aims to identify the causes and effects of farmers' dependence on collectors in the agricultural commodity supply chain. This study uses a qualitative method with a case study approach, through observation, interviews, and documentation, and is analyzed using the Manual Data Analysis Procedure (MDAP). The results of the study show that there is a patronage relationship between farmers and collectors, driven by farmers' limited resources, such as operational capital, land ownership, and infrastructure conditions, as well as differences in socioeconomic status. In this relationship, collectors act as patrons who provide protection and assistance, while farmers as clients are morally bound to sell their produce as a form of loyalty. This patronage relationship is also influenced by kinship ties and emotional closeness, which ultimately strengthen farmers' dependence. The research results provide theoretical benefits as an important reference in agricultural sociology studies on the problems experienced by farmers, especially in the distribution of agricultural commodities. Practically, this research can contribute to the agenda in efforts to realize sustainable development that takes into account the distribution conditions of agricultural commodities owned by local farmers.